Properties of the fullerene C60-containing PN Lin49 in the SMC; Explanations of strong near-IR excess. Issue 5 (July 2016) - Otsuka, Masaaki; Kemper, Francisca; Leal-Ferreira, Marcelo L.; Aleman, Isabel; Bernard-Salas, Jeronimo; Cami, Jan; Ochsendorf, Bram; Peeters, Els
Abstract: We performed a detailed spectroscopic analysis of the fullerene C6 o-containing planetary nebula (PN) Lin49 in the Small Magellanic Cloud (SMC). Lin49 is a C-rich and metal- deficient PN (Z∼⃒0.0006) and its nebular abundances are in agreement with the AGB model for the initially 1.25Mʘ stars with the metallicity Z = 0.001 of Fishlock et al. (2014, [1]). By stellar absorption fitting with TLUSTY, we derived stellar abundances, effective temperature, and surface gravity. We constructed the photo-ionization model with CLOUDY in order to investigate physical conditions of Lin49. The model with the 0.005-0.1 μm radius graphite and a constant hydrogen density shell could not fit the ∼⃒1-5 μm SED owing to the strong near-IR excess. We propose that the near-IR excess indicates (1) the presence of extremely small carbon molecules or (2) the presence of high-density structure surrounding the central star.